Using The Python Library to Create Simple Game Animations - Adi Sadli (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2022)
The development of the game world which has recently been growing rapidly, has aroused the interest of some young people, to become a Maker Game (Game Developer), why this job is in great demand because it looks very cool. Maybe it has crossed our minds when playing games on PC or Mobile how they can make this game. As for Python, it is not only used for programming using Machine Learning models, but also for making games, even the well-known game engines that are commonly used to create complex 2D/3D games such as Unity use Python as a programming language other than C# or C++. Python is the most popular programming language or it would not hurt to say that it is the next generation programming language. In every emerging field in computer science, Python is actively present. Python has an extensive library for various fields such as Artificial intelligence (Pytorch, TensorFlow), Machine Learning (Numpy, Pandas, Matplotlib) and Game development (Pygame,Pyglet). In this opportunity, we will know a little about creating a simple game using the Pygame library (Python library). Pygame is a Python module that is designed for game application development. Pygame is one of the most used libraries/modules. This advantage of pygame allows us to create a game with complete features. Pygame is portable, can run on almost all operating systems. To note, Pygame has been downloaded more than a million times, and millions of visits to the official website. Pygame is released by the GNU General Public License (GPL) so that we can make a game application that is free, open source, shareware, freeware and commercial games. Learning python, of course, must be done gradually and focus on areas of learning that are of interest because of the large number of python modules or libraries with their functions and uses. To become a game developer, we must know the basics of making games, one of which is how to create animations on a game object. Making this game animation only revolves around how to make an object consisting of sprites or several images into animation and use the up, down, left and right arrow keys to move the object. The objects in the game consist of objects commonly called player and opposite.